Security indicators for modern electronic document management systems - I. I. Livshits (Вестник Дагестанского государственного технического университета: Технические науки, 2025)
Objective. Modern electronic document management systems (EDMS) provide controlled movement of multiple documents along different routes. Successful functioning of EDMS is determined by the availability of a specific document at the right time for a specific user. The purpose of the study is to develop a mathematical model of EDMS that allows determining the indicator of ED availability taking into account the UBI and performing optimization taking into account the complex organizational structure. Method. The study was conducted using the apparatus of Markov processes and the formation of numerical safety indicators. Particular attention is paid to the calculations of the numerical indicator of availability. Result. An important attribute has been determined - availability, the numerical indicator of which allows assessing the general level of a specific EDMS and simultaneously solving many specific problems of identifying and countering threats of information blocking, malicious delay in approval, deviation from established routes, which affects availability and, accordingly, the overall level of security. Conclusion. Known types of applied models (functional, set-theoretic, graphtheoretic, probabilistic-parametric) do not allow explicitly forming availability assessments. The proposed model allows identifying vulnerabilities in the EDMS, which can be used to implement new UBI and contribute to increasing the level of information security in EDMS projects.